Prevalence of back pain among high school students in a municipality in southern Brazil - Cíntia Detsch Fonseca; Cláudia Tarragô Candotti; Matias Noll; Anna Maria Hecker Luz; Antônio Cardoso dos Santos; Carlos Otávio Corso
Abstract Objective: To estimate the prevalence of back pain in adolescent girls, and determine whether this pain is associated with socioeconomic, demographic, anthropometric, and behavioral factors. Methods: This was an epidemiological survey with a representative sample of 495 female high school students, aged 14 to 18 years, in the municipality of São Leopoldo in the southern Brazilian state of Rio Grande do Sul. Data were collected through a self-administered questionnaire with closed, standardized, coded, and tested questions. Bivariate analysis included the chi-square test (x2) and calculation of prevalence ratios (α<0.05). Results: The prevalence of back pain was 75.2%. The thoracic-lumbar (30.4%) and lumbar (27.7%) regions of the spine were most affected. Among the students with pain, 60.5% reported the severity of their pain to be moderate to severe, and 21.2% reported that the pain prevented them from performing activities of daily living. Regarding associated factors, the pain was more prevalent in overweight/obese students (RP = 1.246, 95% CI: 1.137 to 1.366), who reported carrying a heavy school backpack/bag (PR = 1.187, 95% CI: 1.073 to 1.314) and those who had incorrect posture when picking up objects from the floor (PR = 1.138, 95% CI: 1.031 to 1.256). Conclusions: There was a high prevalence of back pain associated with body mass index, reported weight of the student's school backpack/bag, and posture when picking up objects from the floor.